Striatal activation and frontostriatal connectivity during non-drug reward anticipation in alcohol dependence - Becker, Alena; Kiefer, Falk; Kirsch, Peter (Addiction biology, 2017)
According to prevailing neurobiological theories of addiction, altered function in neural reward circuitry is a central mechanism of alcohol dependence. Growing evidence postulates that the ventral striatum (VS), as well as areas of the prefrontal cortex, contribute to the increased incentive salience of alcohol-associated cues, diminished motivation to pursue non-drug rewards and weakened strength of inhibitory cognitive control, which are central to addiction. The present study aims to investigate the neural response and functional connectivity underlying monetary, non-drug reward processing in alcohol dependence. We utilized a reward paradigm to investigate the anticipation of monetary reward in 32 alcohol-dependent inpatients and 35 healthy controls. Functional magnetic resonance imaging was used to measure task-related brain activation and connectivity. Alcohol-dependent patients showed increased activation of the VS during anticipation of monetary gain compared with healthy controls. Generalized psychophysiological interaction analyses revealed decreased functional connectivity between the VS and the dorsolateral prefrontal cortex in alcohol dependent patients relative to controls. Increased activation of the VS and reduced frontostriatal connectivity were associated with increased craving. These findings provide evidence that alcohol dependence is rather associated with disrupted integration of striatal and prefrontal processes than with a global reward anticipation deficit.
Gesehen am 24.04.2018